Eating in New Spain, privileges and regrets of society in the XVIII century - Quiróz, Enriqueta (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This paper aims at demonstrating the daily eating habits of the inhabitants of the Viceroyalty of New Spain during the XVIII century. This study seeks to understand thedynamic changes in habits related to coexistence, and the exploitation of the privileged setting of New Spain, from a long term perspective. Eating habits are used to identify social distinctions inherent in eating, which are not directly related to the ethnic background of the population, but to the cost of food and the possibility of obtaining it. Hence, the consumption of privileged sectors, workers, people in extreme poverty and indigenous groups can be identiied.